2020
DOI: 10.1111/jsr.12983
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraceptive use and subjective sleep reports in women: An online survey

Abstract: Female sexual hormones, such as oestrogens and progestagens, have a well-established relationship with human sleep. Progesterone has been described as an important hypnogenic hormone (Andersen, Bittencourt, Antunes, & Tufik, 2006), probably due to its secondary effects as a gabaergic agonist (Lancel, Faulhaber, Holsboer, & Rupprecht, 1996). It also acts as an important respiratory stimulant, promoting increased dilation of the superior airways (Andersen et al., 2006). Oestrogens are also reported as hypnogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The effect on REM latency is inconclusive, as one study found a longer REM latency in women taking hormonal contraceptives [ 70 ] and another study reported a short REM latency in these women [ 57 ]. Other studies reported more sleep disturbances or fatigue [ 63 ] and increased excessive daytime sleepiness [ 76 ] by women using hormonal contraceptives. Women with progestin-only therapies presented shorter sleep duration compared to combined therapy [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect on REM latency is inconclusive, as one study found a longer REM latency in women taking hormonal contraceptives [ 70 ] and another study reported a short REM latency in these women [ 57 ]. Other studies reported more sleep disturbances or fatigue [ 63 ] and increased excessive daytime sleepiness [ 76 ] by women using hormonal contraceptives. Women with progestin-only therapies presented shorter sleep duration compared to combined therapy [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies reported more sleep disturbances or fatigue [ 63 ] and increased excessive daytime sleepiness [ 76 ] by women using hormonal contraceptives. Women with progestin-only therapies presented shorter sleep duration compared to combined therapy [ 76 ]. Another study found that women taking monophasic combined oral contraceptives had more stage 2 sleep and less deep sleep [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 122 were analysed in the second step, based on a reading of the full texts. The final sample comprised 13 articles (Albuquerque et al, 2015; Baker, Mitchell et al, 2001a; Baker, Waner et al, 2001b; Bezerra et al, 2020; Burdick et al, 2002; Costa et al, 2017; Guillermo et al, 2010; Hachul et al, 2013; Hachul et al, 2010; Hachul et al, 2020; Hicks & Cavanaugh, 1982; Kalleinen et al, 2008; Plamberger et al, 2021), and included 2775 individuals (HCU: 1270; NCU: 1505). The article selection process is described in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…For example, research finds that women on first and second generation HCs -which are more androgenic than subsequent generations of HCs -often experience a greater number of masculinizing side effects, such as acne, hirsutism, and scalp hair loss, than women on later generations of products (Jones, 1995). Others have found that the progestin generation in women's HCs moderate their impact on women's sleep quality (Bezerra et al, 2020), sexual function (Shahnazi et al, 2015), and the responsiveness of the HPA axis to stress . For example, in one study, researchers found that women using OCs containing first and third generation progestins exhibited a blunted HPA axis response to acute stress, whereas women using OCs containing second generation progestins were spared from this effect, exhibiting normal HPA axis function .…”
Section: Prescription-based Factorsmentioning
confidence: 99%